Analysis of the Chunking Process in RAG Architectures - Amaral, Vitor Mateus R. do; Espinosa, Luiza; Lunardi, Gabriel M.; Oliveira, Adriano Q. de; Silveira, Thiago Lopes T. da; Emmendorfer, Leonardo R. (Anais da Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul (ERAMIA-RS); 2025: Anais da I Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região SulDO - 10.5753/eramiars.2025.16765, 2025)
This paper studies how text segmentation affects Retrieval Augmented Generation. We compare heuristic, semantic, and recursive strategies on a Portuguese institutional corpus, holding the pipeline fixed with bge base en v1.5 embeddings, a 500 token target size, and about 10% overlap. In the semantic variant, boundaries are detected by changes in similarity between sentence embeddings using a 95th percentile threshold. Evaluation covers intrinsic coherence and extrinsic metrics such as Factual Accuracy, Precision, Recall, F1-score, and MRR.